Moringa Oleifera Coagulation Characteristics in Wastewater Treatment in a University Dormitory - M. S. Ogunshina, O. M. Abioye, K. A. Adeniran and D. A. Olasehinde (Nature Environment and Pollution Technology, 2023)
Wastewater treatment necessitates the use of an appropriate method to achieve satisfactory results. The conventional method of Alum addition has been widely used for years, but it is prohibitively expensive. This study uses Moringa oleifera, an inexpensive and readily available plant, as a natural coagulant to treat wastewater collected from university dormitories. Physicochemical parameters such as pH, Turbidity, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Dissolved Oxygen (DO) were examined based on appropriate standards. Wastewater treatment with varied coagulant dosages of 50, 100, and 150 mg.L-1) was monitored using a standard jar test device with an initial wastewater perturbation at 100 rpm for 5 min was reduced to 50 rpm in 10 minutes with a rest time of 30 min. The results showed that the quality of the physicochemical properties of the water improved. The percentage increase in the water quality is; BOD (92%), COD (92%), and TDS (52-64%), with an increase in Moringa coagulant achieving a reduction of 96% of Turbidity. While the DO improved (79%), the pH remained below acceptable limits (6.73-7.56) for effluent disposal. The treated water showed clarity (colorless) and no odor compared to the wastewater. Hence, Moringa oleifera seeds cake residue can be an effective coagulant for wastewater treatment.